Deleting an Nr4a1 super-enhancer subdomain ablates Ly6C(low) monocytes while preserving macrophage gene function - Thomas, Graham D. (Immunity, 2016)
Mononuclear phagocytes are a heterogeneous family that occupy all tissues and assume numerous roles to support tissue function and systemic homeostasis. Our ability to dissect the roles of individual subsets is limited by a lack of technologies that ablate gene function within specific mononuclear phagocyte sub-populations. Using Nr4a1-dependent Ly6C(low) monocytes we present a proof-of-principle approach that addresses these limitations. Combining ChIP-Seq and molecular approaches we identified a single, conserved, sub-domain within the Nr4a1 enhancer that was essential for Ly6C(low) monocyte development. Mice lacking this enhancer lacked Ly6C(low) monocytes but retained Nr4a1 gene expression in macrophages during steady state and in response to LPS. As Nr4a1 regulates inflammatory gene expression and differentiation of Ly6C(low) monocytes, decoupling these processes allows Ly6C(low) monocytes to be studied independently.